2020
DOI: 10.1002/nop2.566
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing improved assessment and control of pain in end‐of‐life care when using the Abbey Pain Scale systematically

Abstract: People with cognitive impairment at the end-of-life care (EoL care) often have their pain underdiagnosed and undertreated due to the lack of knowledge and lack of guidelines for systematic pain assessment. According to recommendations from The National Board of Health and Welfar [Socialstyrelsen] (2013a), systematic pain assessments in EoL care should have high priority in providing optimal treatment of pain. In Sweden, about 90,000 people die annually and it is estimated that about 80% of these would benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Across all settings, implementation of systematic pain assessment measures, specifically among nurses, has been shown to improve pain control at the end of life and can help change the attitudes regarding use of the measures. 19,20 Within our study, an improvement in knowledge may not have been consistently demonstrated because almost 50% of participants reported 1 or more years of experience with hospice and palliative care. Therefore, it is likely there would not be a drastic improvement in these participants.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Across all settings, implementation of systematic pain assessment measures, specifically among nurses, has been shown to improve pain control at the end of life and can help change the attitudes regarding use of the measures. 19,20 Within our study, an improvement in knowledge may not have been consistently demonstrated because almost 50% of participants reported 1 or more years of experience with hospice and palliative care. Therefore, it is likely there would not be a drastic improvement in these participants.…”
Section: Discussionmentioning
confidence: 77%
“…Results indicate that clinicians feel more confident and have a higher preference in using the previously mentioned pain assessment strategies and measures after the training. Across all settings, implementation of systematic pain assessment measures, specifically among nurses, has been shown to improve pain control at the end of life and can help change the attitudes regarding use of the measures 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Participants felt that the APS-SE score was a better indicator of suffering in general than of pain in particular. A crucial problem, the difficulty of distinguishing between pain and anxiety, has been noted by others [19]. Not knowing whether the patient is suffering pain or something else makes it difficult to decide how to provide relief.…”
Section: Discussionmentioning
confidence: 99%
“…The APS has been translated and the tested for validity in Italy [15], Japan [16], Spain [17], and Denmark [18]. Nursing home staff perceived the APS to improve systematic pain assessment [19], and Manias and colleagues suggested it could confirm self-reported pain in older patients [20]. The tool has been available in Sweden since 2011, distributed mainly through the Swedish Register of Palliative Care (SRPC) [21].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of an earlier Swedish version of the APS in residential aged care facilities in 2012 was perceived by staff to take time, but to improve their ability to detect and assess pain. When interviewed a year after the implementation, staff stressed the need for further education and training and recommended required routines for pain assessment (Ludvigsson et al, 2020 ). To ensure better care for elderly people in Sweden, the Swedish National Board of Health and Welfare will invest roughly 100 million euros from 2022 to 2023 to increase the number of nurses working in residential care facilities (Swedish National Board of Health and Welfare, 2022 ).…”
Section: Discussionmentioning
confidence: 99%